Profesionalisme Guru PAI Berbasis Digitalisasi pada Era Sosiety 5.0 di SMP Negeri 2 Mojoagung Jombang - Shafira Nadia; Mohammad Saat Ibnu Waqfin (ISLAMIKA, 2023)
Advances in digital media have changed the thinking of professional educators about how to achieve education and continue to develop so that students are not left behind. It is important to use digital media correctly so that students can understand the material well. This study aims to 1.) Know the role of Islamic religious education teachers in facing the era of Society 5.0. 2) Finding innovation and application of Islamic Religious Education learning teachers to face the Society 5.0 era. The types and sources of data used are primary and secondary data by analyzing data validity techniques. The method used in this research is descriptive qualitative research. Methods of data collection in this study using observation, interviews and documents. The results of this study show the important role of teachers in the digital era and the teaching methods used by teachers to convey the learning process. By continuing to use digital media can help students understand the material better.